Haptoglobin, alpha-thalassaemia and glucose-6-phosphate dehydrogenase polymorphisms and risk of abnormal transcranial Doppler among patients with sickle cell anaemia in Tanzania - Cox, SE; Makani, J; Soka, D; L'Esperence, V; Kija, E; Dominguez-Salas, P; Newton, C; Birch, A; Prentice, A; Kirkham, F (Blackwell Publishing Ltd, 2014)
Transcranial Doppler ultrasonography measures cerebral blood flow velocity (CBFv) of basal intracranial vessels and is used clinically to detect stroke risk in children with sickle cell anaemia (SCA). Co-inheritance in SCA of alpha-thalassaemia and glucose-6-phosphate dehydrogenase (G6PD) polymorphisms is reported to associate with high CBFv and/or risk of stroke. The effect of a common functional polymorphism of haptoglobin (HP) is unknown. We investigated the effect of co-inheritance of these polymorphisms on CBFv in 601 stroke-free Tanzanian SCA patients aged <24 years. Homozygosity for alpha-thalassaemia 3·7 deletion was significantly associated with reduced mean CBFv compared to wild-type (β-coefficient -16·1 cm/s, P = 0·002) adjusted for age and survey year. Inheritance of 1 or 2 alpha-thalassaemia deletions was associated with decreased risk of abnormally high CBFv, compared to published data from Kenyan healthy control children (Relative risk ratio [RRR] = 0·53 [95% confidence interval (CI):0·35-0·8] and RRR = 0·43 [95% CI:0·23-0·78]), and reduced risk of abnormally low CBFv for 1 deletion only (RRR = 0·38 [95% CI:0·17-0·83]). No effects were observed for G6PD or HP polymorphisms. This is the first report of the effects of co-inheritance of common polymorphisms, including the HP polymorphism, on CBFv in SCA patients resident in Africa and confirms the importance of alpha-thalassaemia in reducing risk of abnormal CBFv. © 2014 The Authors. British Journal of Haematology Published by John Wiley and Sons Ltd.